2019
DOI: 10.3892/ol.2019.10056
|View full text |Cite
|
Sign up to set email alerts
|

Expression of integrin α‑6 is associated with multi drug resistance and prognosis in ovarian cancer

Abstract: Ovarian cancer is a serious threat to women's health. Multidrug resistance is a major cause of post-treatment relapse, metastasis, and even mortality. This characteristic severely restricts the survival of patients with ovarian cancer. Integrin α-6 (ITGA6) is a member of the adhesion molecule family that conducts signals through interactions between the extracellular domain and the matrix, serving important roles in cell adhesion-mediated drug resistance, which is considered to have a critical function in ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The integrin subtypes α6, αV, β1, and β4 were also significantly increased under chronic everolimus exposure. α6 has been shown to induce cell motility and invasion and promote drug resistance [ 25 , 26 ] and might, therefore, be partially responsible for reactivating the tumor cell invasion cascade by everolimus. This integrin subtype was not further investigated, since in RT112 cells, it was not as strongly influenced by drug exposure as were other integrin subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The integrin subtypes α6, αV, β1, and β4 were also significantly increased under chronic everolimus exposure. α6 has been shown to induce cell motility and invasion and promote drug resistance [ 25 , 26 ] and might, therefore, be partially responsible for reactivating the tumor cell invasion cascade by everolimus. This integrin subtype was not further investigated, since in RT112 cells, it was not as strongly influenced by drug exposure as were other integrin subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Song et al have unveiled that OIP5-AS1 was highly expressed in cervical cancer tissues [9]. A previous study has suggested that miR-92a was downregulated in breast cancer cells [16], and it has been identi ed that the expression of ITGA6 was increased in cisplatin-resistant SKOV3 and cisplatin-resistant A2780 cells, and also in drug-resistant tissues in comparison to the controls [18]. The relationship between OIP5-AS1 and clinicopathological characteristics of OC patients has been analyzed and we discovered that the high expression of OIP5-AS1…”
Section: Discussionmentioning
confidence: 70%
“…Nevertheless, the combined effect of OIP5-AS1 and miR-92a is still unexplored. Integrin alpha 6 (ITGA6) is a 150-kDa transmembrane protein [17] that has been revealed to be related to drug resistance and prognosis in OC [18]. However, the target relation between miR-92a and ITGA6 remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the Coremine database was widely used to find new therapeutic targets and mechanism analysis, especially in the analysis of chemotherapy resistance mechanisms. 53,54 Therefore, after cross-alignment by coremine database, LMO7, SMURF1, BCL2L1 and STAT3 were identified as the primary hubgenes. Afterwards, we continued to evaluate the association between hubgenes and the prognosis of gastric cancer patients by THPA.…”
Section: Discussionmentioning
confidence: 99%